THE ANALYSIS OF SELF-CONTROL TOWARDS THE COMMUNITY DISOBEDIENCE ON REGIONAL REGULATION CONCERNING NONSMOKING AREA AT HOSPITAL OF UNIVERSITAS HASANUDDIN - Mawardi Shabir, Achmad; Palutturi, Sukri; Suriah (International Journal of Psychosocial Rehabilitation, 2020)
Non-Smoking Area policy in hospital has been established for long time as an intervention strategy to control non-communicable disease. Regional regulation regarding Non-Smoking Area also has been approved by various countries as a regulation embodiment of tobacco throughout the world. Regional policy that has been issued must be implemented by all regional government in Indonesia. The present research discussed factors related to the community in Non-Smoking Area in the Hospital of Universitas Hasanuddin. This quantitative research was conducted using cross-sectional study. The total research samples were 100 people selected through non-probability sampling using convenience sampling technique. The data collected were then processed and analyzed using statistical test of Chi-Square Test. Based on the analysis performed, it was obtained that there was a relationship between understanding on instruction (p=0.023), belief (p=0.006), attitude (p=0.000) and self-control (p=0.000) on the community disobedient on the regional regulation concerning non-smoking area in the Hospital of Universitas Hasanuddin. It is suggested that the government can reevaluate the regional regulation concerning the non-smoking area in the hospital to support positive change of smoking behavior such as decreasing ad stopping smoking in the hospital. It is also suggested to the management of the hospital to be better and more assertive in implementing the non-smoking area policy so that the smoking attitude can be decreased and controlled more. The health workers are also expected to be more active in promoting and socializing the danger of smoking and smoking prohibition in the hospital by decisively follow up the smoker who disobedient towards the policy.